2019
DOI: 10.1016/j.celrep.2019.03.059
|View full text |Cite
|
Sign up to set email alerts
|

Qa-1-Restricted CD8+ T Cells Can Compensate for the Absence of Conventional T Cells during Viral Infection

Abstract: SUMMARY The role of non-classical T cells during viral infection remains poorly understood. Using the well-established murine model of CMV infection (MCMV) and mice deficient in MHC class Ia molecules, we found that non-classical CD8 + T cells robustly expand after MCMV challenge, become highly activated effectors, and are capable of forming durable memory. Interestingly, although these cells are restricted by MHC class Ib molecules, they respond similarly to conventional T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 78 publications
(91 reference statements)
1
20
0
Order By: Relevance
“…These studies appear to suggest that HLA-E-restricted CD8 + T cells act as effector cells rather than Treg cells in patients with infectious diseases. These findings are similar to some findings on Qa-1-restricted CD8 + T cells in animal infections [82]. However, studies of animal infections also suggest that Qa-1-restricted CD8 + T cells are Treg cells during infections [59].…”
Section: Current Status Of Human Studiessupporting
confidence: 90%
See 2 more Smart Citations
“…These studies appear to suggest that HLA-E-restricted CD8 + T cells act as effector cells rather than Treg cells in patients with infectious diseases. These findings are similar to some findings on Qa-1-restricted CD8 + T cells in animal infections [82]. However, studies of animal infections also suggest that Qa-1-restricted CD8 + T cells are Treg cells during infections [59].…”
Section: Current Status Of Human Studiessupporting
confidence: 90%
“…Studies of these mice showed that CD8 + T cells acted similarly to conventional CD8 + T cells (i.e., those CD8 + T cells that are restricted by MHC class Ia molecules), formed memory, and protected the mice from lethality during cytomegalovirus infection. Interestingly, Qa-1-restricted CD8 + T cells constituted a large and critical portion of the effector population [82]. Therefore, the previous findings on the paradoxical roles of Qa-1-restricted CD8 + T cells in infections are strikingly similar to those in cancers.…”
Section: Harnessing Qa-1-restricted Cd8+ Treg Cells For the Treatmmentioning
confidence: 92%
See 1 more Smart Citation
“…NKG2A interaction with Qa-1b can also limit the activation levels of virus specific CD8+ T cells in acute poxvirus infection resulting in reduced activation induced cell death and better antigen specific CD8+ T cell responses and control of virus (Fang et al, 2011 ; Rapaport et al, 2015 ). Interestingly, Qa-1b also is important for the development of protective non-conventional CD8+ T cell responses in the salivary gland of mice during acute MCMV infection in the absence of conventional CD8+ T cells (Anderson et al, 2019 ). Much of what is understood about NKG2A-Qa-1b interactions is in the context of acute infections.…”
Section: Discussionmentioning
confidence: 99%
“…In normal conditions, Qa‐1‐restricted CD8 + T cells suppress excessive B‐cell activation by reducing CD4 + T follicular helper cells. However, this is not their exclusive function as they have been shown to act as potent effectors in viral and bacterial infections [137, 143].…”
Section: Qa‐1‐restricted T Cellsmentioning
confidence: 99%